A General Method for Insertion of Functional Proteins within Proteins via Combinatorial Selection of Permissive Junctions. Issue 8 (20th August 2015) - Peng, Yingjie; Zeng, Wenwen; Ye, Hui; Han, Kyung Ho; Dharmarajan, Venkatasubramanian; Novick, Scott; Wilson, Ian A.; Griffin, Patrick R.; Friedman, Jeffrey M.; Lerner, Richard A.
Summary: A major goal of modern protein chemistry is to create new proteins with different functions. One approach is to amalgamate secondary and tertiary structures from different proteins. This is difficult for several reasons, not the least of which is the fact that the junctions between secondary and tertiary structures are not degenerate and usually affect the function and folding of the entire complex. Here, we offer a solution to this problem by coupling a large combinatorial library of about 10 7 different N- and C-terminal junctions to a powerful system that selects for function. Using this approach, the entire Leptin and follicle-stimulating hormone (FSH) were inserted into an antibody. Complexes with full retention of function in vivo and in vitro, although rare, were found easily by using an autocrine selection system to search for hormonal activity. Such large diversity systems, when coupled to robust selection systems, should enable construction of novel therapeutic proteins. Graphical Abstract: Highlights: Robust high-throughput screening-based method for inserting proteins into proteins Functional Leptin in human IgG with longer serum half-life in vivo than native Leptin Single-chain FSH in human IgG with similar activity compared with native FSH Abstract : Peng et al. report a general approach based on robust high-throughput screening for inserting functional proteins into proteins. The selected Leptin and single-chain FSH in human IgG were as potent as the native hormones.